PARADIGMA ISLAM DAN EKONOMI PADA MASA KHULAFAU AR-RASYIDDIN - Abdul Husenudin; Jamaludin (Program Studi Ekonomi Syariah, 2023)
The authorship of this article is intended to discuss the paradigm and dynamics of Islamic economic thought during the time of Khulafau Ar-Rashiddin, who, although both applied Islamic economics, differed in the policies created in each era of leadership. Literature study (Library Research) was chosen as the research method, that is, reference sources and discussions related to titles were taken from books, journals, research results, etc. Originally the practice of Islamic economics in trading activities, fiscal and monetary policies had the Prophet Muhammad. do it. Then the mandate for the leadership of the Muslim community was given to the four khulafau ar-Rashiddin, after he died. During the time of Abu Bakr many people rebelled (apostates and refused zakat). In the era of Umar Bin Khattab, set aside some of the assets in the baitul mal as a reserve fund. Politics heated up and slander spread widely, Uthman Bin Affan's leadership period was marked by issues of nepotism. Finally, printing coins on behalf of an Islamic state was a policy during the leadership of Ali bin Abi Thalib